New species and additional records of Tetrabothrus Bernhauer from China (Coleoptera, Staphylinidae, Aleocharinae) - Yan, Zhu-Qi; Li, Li-Zhen (Zootaxa, 2015)
Material of the lomechusine genus Tetrabothrus Bernhauer, 1915 from China was studied. A new species is described and illustrated under the name T. xizangensis Z.-Q. Yan and L.-Z. Li, sp. nov. (Xizang). Tetrabothrus japonicus is reported in China for the first time, and the new locality for T. puezti and T. inflexus are given. All Chinese species are mapped, and an identification key is provided.